Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning dalam Pembelajaran PAI Dan Budi Pekerti Kelas IV SD Negeri 13 Serasi - Siregar, Nurkholila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to enhance the quality of learning through the implementation of an experiential learning model in the classroom. The model is based on psychological theories of education, such as those by Piaget, Vygotsky, and Kolb, which emphasize the importance of direct experience and social interaction in the learning process. The research was conducted in two cycles, with Cycle I showing some challenges in implementing the model, but Cycle II showing significant improvements in student engagement and performance. The findings of this study indicate that experiential learning can improve students' understanding, enhance their social skills, and create a more interactive and enjoyable learning environment. Experiential learning proves to be effective in supporting students' cognitive and social development overall.